Implementing Curriculum Adjustment for Christian Education and Theology Study Programs Based on Merdeka Belajar Kampus Merdeka - Lince Sihombing (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
In Indonesia, even though its demography is noted as the fourth largest population in the world, its significant number does not give a positive effect on graduates of Christian Institutions. It is so since Christian inhabitants in Indonesia are a minority while the institution run by these Christian and Theology Study Programs are abundant. It causes graduates from these institutions over the capacity for schools and churches can use. In order to increase the opportunity for taking jobs for graduates of Theological Institutions, there must be innovative ways taken. This research was conducted by qualitative method with phenomenological approach. The research’s object was students and graduates of Institut Agama Kristen Negeri (IAKN) Tarutung since 2016. The research’s result showed that Merdeka Belajar Kampus Merdeka (MBKM) could be good solution for the problem. MBKM can help students gain experience outside of their study program, which will be needed when they graduate and start to seek for a job.